Central nervous targets for the treatment of bladder dysfunction. Issue 1 (5th July 2013) - Yoshimura, Naoki; Miyazato, Minoru; Kitta, Takeya; Yoshikawa, Satoru
Abstract Background The functions of the lower urinary tract, to store and periodically release urine, are dependent on the activity of smooth and striated muscles in the urinary bladder, urethra, and external urethral sphincter. This activity is in turn controlled by neural circuits in the brain, spinal cord, and peripheral ganglia. Aims This paper will review recent advances in our understanding of the pathophysiology of voiding disorders, especially focusing on the central nervous system. Methods Various neurotransmitters, including acetylcholine, norepinephrine, dopamine, serotonin, excitatory and inhibitory amino acids, adenosine triphosphate, nitric oxide, and neuropeptides, have been implicated in the neural regulation of the lower urinary tract. Results Injuries or diseases of the nervous system, as well as drugs and disorders of the peripheral organs, can produce voiding dysfunctions such as urinary frequency, urgency, or incontinence. Conclusion We discuss the potential targets in the central nervous system and new modalities for the treatment of voiding dysfunction. Neurourol. Urodynam. 33:59–66, 2014. © 2013 Wiley Periodicals, Inc.